Determination of bearing capacity factor Nc for circular piles in clays by using lower bound finite element analysis - Chakraborty M.; Prasad S.D. (My University, 2025)
The aim of this present paper is to provide lower bound bearing capacity factor Nc for axially loaded circular piles in clays by using two-dimensional finite elements and the three-dimensional non-linear Tresca yield criterion. The clay layer is assumed to be completely saturated and subjected to undrained loading. The edge discontinuities of the Tresca surface was smoothened by providing a C 2 rounded surface at the vicinity of the sharp corners of the regular hexagon lying on the octahedral plane. No inherent assumption of hoop stress was considered in the present analysis. The clay has been considered to be heterogeneous where the cohesion increases linearly with depth. The study is useful in providing the methodology for simulating the axisymmetric structures and providing the design chart for the bearing capacity factors for circular piles in clays whose cohesion increases linearly with depth. © 2019 Informa UK Limited, trading as Taylor & Francis Group.